2020
DOI: 10.18697/ajfand.89.17520
|View full text |Cite
|
Sign up to set email alerts
|

High variability of iodine in iodized salt and urine from rural households in Sidama zone, Southern Ethiopia: A cross-sectional study

Abstract: Iodine is essential for the synthesis of thyroid hormones which regulate the metabolic processes of most cells and play important roles in human growth and development. Iodine deficiency has long been one of the most common nutritional problems in the world. Ethiopia, particularly the study population (Sidama) has a history of severe iodine deficiency. The purpose of the study was to assess urinary iodine concentration, level of goiter in mothers and school-age children and household salt iodine concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This may be because members of the households do not understand or cannot comprehend the exact expiration date and iodized salt notifications. Similar research by Arba Minch (30) showed that the adequacy of iodized salt in household salt was not found to be associated with food handler knowledge or practice (30).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This may be because members of the households do not understand or cannot comprehend the exact expiration date and iodized salt notifications. Similar research by Arba Minch (30) showed that the adequacy of iodized salt in household salt was not found to be associated with food handler knowledge or practice (30).…”
Section: Discussionmentioning
confidence: 73%
“…The World Health Organization's goal of eradicating iodine deficiency illnesses (≥90%) is substantially exceeded by this finding (1). According to the findings of this study, the proportion of households with adequate iodized salt is less than in earlier studies from Combolcha (68.8%) (25), Assella (62.5%) (26), and Dera (57.4%) (27), Oromia Regional State, South East Ethiopia (61.1%) (28), Southeast Ethiopia (56.6%) (28), Kolfe Keraniyo, Addis Ababa (95.5%) (29), Sidama Zone (65%) (30), China (89%) (31), Ghana (75.6%) (32), and India (75%) (33). This may be a result of the market's accessibility and availability of iodized salt, as well as laws, policies, and ongoing follow-up and monitoring of the use of iodized salt in various nations.…”
Section: Discussionmentioning
confidence: 74%